A Hubel Wiesel model for hierarchical representation of concepts in textual documents - RAMANATHAN, Kiruthika (Institutional Knowledge at Singapore Management University, 2010)
Hubel Weisel models of the cortex describe visual processing as a hierarchy of increasingly sophisticated representations. While several models exist for image processing, little work has been done with Hubel Weisel models out of the domain of object recognition. In this paper, we describe how such models can be extended to the representation of concepts, resulting in a model that shares several properties with the PDP model of semantic cognition. The model that we propose is also capable of incremental learning, in which the knowledge is stored in the strength of the neuron connections. Degradation of old knowledge occurs as new knowledge is introduced to the system in a fashion that simulates decay theory in short term memory. The simulation model therefore captures several properties of cognitive conceptual memory, including generalization patterns, the role of rehearsal and, hierarchical representation.